The Effectiveness of Using Coloured Blocks in Teaching the Concept of Balancing Chemical Equation in Chemistry - Ridzuan, Razreena; H Iksan, Zanaton (Journal of Educational Sciences, 2017)
The aim of this study is to study the effectiveness of usingcoloured blocks in teaching the concept of balancing chemical equation inchemistry. It is expected that students will improve their understanding inthis concept and students interest in chemistry.  This study examined how byusing coloured blocks will help students understand the concept of balancingchemical equation which is an important concept to master in Form 4Chemistry. Using pre and post-test control group design, the study involveda comparison between a control group (n=20) which were taught using theconventional chalk and talk method to balance chemical equation while thetreatment group (n=20) were taught to balance chemical equations usingcoloured blocks. After pre-test, there was a significant difference betweencontrol and treatment group on their post-test scores with effect size of 1.31.Students who had used coloured blocks to balance chemical equationsshowed significant development in their post-test compared to the studentswho were taught using the conventional method. Students also showed highinterest in chemistry upon using coloured blocks in teaching the concept ofbalancing chemical equation. The research results recommended the use ofcoloured blocks as a potential tool to teach the concept of balancingchemical equations.